Companionship during facility-based childbirth: results from a mixed-methods study with recently delivered women and providers in Kenya - Patience Afulani; Caroline Kusi; Leah Kirumbi; Dilys Walker (BMC, 2018)
Abstract Background Research suggests that birth companionship, and in particular, continuous support during labor and delivery, can improve women's childbirth experience and birth outcomes. Yet, little is known about the extent to which birth companionship is practiced, as well as women and providers' perceptions of it in low-resource settings. This study aimed to assess the prevalence and determinants of birth companionship, and women and providers' perceptions of it in health facilities in a rural County in Western Kenya. Methods We used quantitative and qualitative data from 3 sources: surveys with 877 women, 8 focus group discussions with 58 women, and in-depth interviews with 49 maternity providers in the County. Eligible women were 15 to 49 years old and delivered in the 9 weeks preceding the study. Results About 88% of women were accompanied by someone from their social network to the health facility during their childbirth, with 29% accompanied by a male partner. Sixty-seven percent were allowed continuous support during labor, but only 29% were allowed continuous support during delivery. Eighteen percent did not desire companionship during labor and 63% did not desire it during delivery. Literate, wealthy, and employed women, as well as women who delivered in health centers and did not experience birth complications, were more likely to be allowed continuous support during labor. Most women desired a companion during labor to attend to their needs. Reasons for not desiring companions included embarrassment and fear of gossip and abuse. Most providers recommended birth companionship, but stated that it is often not possible due to privacy concerns and other reasons mainly related to distrust of companions. Providers perceive companions' roles more in terms of assisting them with non-clinical tasks than providing emotional support to women. Conclusion Although many women desire birth companionship, their desires differ across the labor and delivery continuum, with most desiring companionship during labor but not at the time of delivery. Most, however, don't get continuous support during labor and delivery. Interventions with women, companions, and providers, as well as structural and health system interventions, are needed to promote continuous support during labor and delivery.